Guidelines of interfaith dialogue in Malaysia context: An Islamic perspective - Aman Daima, Md. Zain; Mohd Safri, Ali; Syed Hadzrullathfi, Syed Omar; Wan Mohd Khairul Firdaus, Wan Khairuldin (2019)
The study of religion emphasized on the objectivity and scientific approaches. Different approaches have been used in interfaith dialogue within the Islamic framework in order to create a harmonious platform of discussion between religions. Religious polemic, within an extreme platform, could risk the build of society at many levels as well as affecting religious tolerance among society with different backgrounds of races and religions. In the context of Malaysia, the implementation of interfaith dialogue has been a common practice organized by different organizations which involved common values and different approaches. This paper is to significantly address the guidelines in conducting interfaith dialogue in the context of Malaysia and the adaptation of those approaches to improve religious tolerance in Malaysia. The methodology adopted for this paper is the qualitative approach which included literature review, observation as well as particular interviews with three people who represented different religious organizations. The finding shows that even though interfaith dialogue has been acknowledged as the best platform for religious discussions, there are still possible improvements and suggestions to be implemented in its establishment.